THE STUDENTS’ DIFFICULTIES IN WRITING THESIS STATEMENT - Dini Hadiani (Jurnal Semantik, 2013)
This study is aimed at identifying the students’ ability in writing thesis statement. By implementing descriptive method, twelve students’ texts were analyzed and the focuswas on the introduction section of their essays. Interview was conducted to justifythe result of students’ text analysis, and also to find out the problems they faced inthe process of writing and the possible solutions. The result showed that the mainproblems were on the grammar rules of the essay and how the ideas were delivered.These were mostly caused by the low capacity of the students’ grammaticalcompetence. It is therefore suggested that the teacher should give various exercisesin the use of grammar of essay writing and how the ideas could be delivered well.Keywords: writing, thesis statement, grammar rules